Understanding Tuberculosis: Perspectives and Experiences of the People of Sabah, East Malaysia (Journal of Health, Population and Nutrition, 2010)
Malaysia is a country with the intermediate burden of tuberculosis (TB). TB is still a public-health problem in Sabah, one of the two states in East Malaysia. In 2007, the state of Sabah contributed slightly more than 3,000 of 16,129 new and relapse cases reported in the country. It has a notification rate of two and a half times that of the country's. Very few studies on TB have been conducted in Sabah, and there is little documentation on the perceptions of TB patients and the community about TB, healthcare-seeking behaviour, and impact of TB on the people of Sabah. A qualitative study was conducted in 2006 in seven districts in Sabah to assess the knowledge and perceptions of TB patients and the community about TB, also to know the experiences of healthcare services, and to examine the impact of TB on patients and families. Purposive sampling identified 27 TB patients and 20 relatives and community members who were interviewed using a set of questions on knowledge, perceptions about TB, healthcare-seeking behaviour, and impact of TB. A further 11 health staff attended informal discussions and feedback sessions. Most interviews were taped and later translated. Data were analyzed using thematic content analysis. Ninety-six percent of the respondents did not know the cause of TB. Some thought that TB occurred due to a ‘tear' in the body or due to hard work or inflammation while others thought that it occurred due to eating contaminated food or due to sharing utensils or breathing space with TB patients. Although the germ theory was not well-known, 98% of the respondents believed that TB was infectious. Some patients did not perceive the symptoms they had as those of TB. The prevailing practice among the respondents was to seek modern medicine for cure. Other forms of treatment, such as traditional medicine, were sought if modern medicine failed to cure the disease. TB was still a stigmatizing disease, and the expression of this was in both perceived and enacted ways. TB also affected the patients in various aspects of their lives, such as psychosocial, physical, financial and life practices. Patients who were farmers complained that they did not recover fully from their disease and were not, thus, able to continue with their previous work. Patients changed their life practices, such as not sharing their utensils, had a separate sleeping area, and practised social distancing. On the other hand, most health workers were unaware of the effects of TB on their patients and that knowledge of their patients on TB was inadequate. There is a need to understand the reasons for the misconceptions about TB and to address the lack of knowledge on TB through health education. Patients need to recognize the symptoms of TB early so that prompt treatment can be initiated, and patients need to be convinced of its curability. Key words: Knowledge attitudes and practices; Qualitative studies; Perceptions; Tuberculosis; Malaysia DOI: 10.3329/jhpn.v28i2.4880 J Health Popul Nutr 2010 Apr; 28(2): 114-123